Feed Conversion Efficiency, Milk Production and Methane Emission in Cows Fed Balanced Rations Containing Bypass Protein Feed - Hossain, S. A.; Sherasia, P. L.; Phondba, B. T.; Patel, B. P.; Garg, M. R. (Indian Journal of Animal Nutrition, 2017)
A field study was conducted on early lactating crossbred cows (n=27) to evaluate the effect of feeding balanced rations containing bypass protein feed on feed conversion efficiency (FCE), milk production, metabolic profile and enteric methane emission. Nutritional status of animals before feeding balanced ration was assessed by using ration balancing software developed by NDDB. Thereafter, the ration of each cow was balanced as per individual’s nutritional requirements and fed for 40 days. Feeding practice revealed that dietary intake of protein and energy was higher by 9.9 and 5.0%, respectively whereas calcium and phosphorus intake was lower by 33.9 and 27.0%, respectively than the requirements of cows. Balanced feeding improved (P<0.01) daily milk yield and fat corrected milk (FCM) by 4.5 and 8.0%, respectively whereas cost of milk production (`/kg FCM) reduced by 8.6% (P<0.01). Feed conversion efficiency (FCE) and nitrogen use efficiency (NUE) improved (P<0.01) by 12.3 and 19.0%, respectively after feeding balanced rations in cows. Balanced feeding reduced (P<0.05) faecal nitrogen loss and parasitic infestation by 10.0 and 44.4%, respectively. Level of immunoglobulin IgA increased by 37.5% (P<0.01) whereas blood urea nitrogen reduced by 33.2% (P<0.01) after feeding balanced rations in cows. Balanced feeding included bypass protein feed reduced (P<0.01) enteric methane emission by 13.5 and 17.9% when expressed in terms of g/d and g/kg milk yield, respectively. Hence, balanced feeding with higher rumen un-degradable protein has potential for improving FCE, NUE, milk production, health status and reducing enteric methane emission in dairy cows.